Prognostic significance of 1p36 locus deletion in adenoid cystic carcinoma of the salivary glands - Šteiner, Petr; Andreasen, Simon; Grossmann, Petr; Hauer, Lukáš; Vaněček, Tomáš; Miesbauerová, Markéta; Santana, Thalita; Kiss, Katalin; Slouka, David; Skálová, Alena (Virchows Archiv, 2018)
Adenoid cystic carcinoma (AdCC) of the salivary glands is characterized by MYB-NFIB or MYBL1-NFIB fusion, prolonged but relentlessly progressive clinical course with frequent recurrences, and development of distant metastasis resulting in high long-term mortality. Currently, no effective therapy is available for patients with advanced non-resectable and/or metastatic disease. Complicating the clinical management of this patient group is the lack of prognostic markers. The purpose of this study is to investigate the prognostic value of 1p36 loss in patients with AdCC. The presence of 1p36 deletion and gene fusions involving the MYB, NFIB, and MYBL1 genes in a cohort of 93 salivary gland AdCCs was studied using fluorescence in situ hybridization. These results were statistically correlated with clinical data and outcome. Deletion of 1p36 in AdCC was identified in 13 of 85 analyzable cases (15.29%). MYB-NFIB fusion was detected in 57/85 (67.1%), MYBL1-NFIB fusion in 12/85 (14.1%), MYB-X fusion in 4/85 (4.7%), MYBL1-X in 4/85 (4.7%), and NFIB-X in 2/85 (2.4%) of AdCC cases. None of the 1p36-deleted samples showed MYBL1 rearrangement. Statistical analysis demonstrated a significant correlation between 1p36 deletion and advanced tumor stage and solid histology (p = 0.0061 and 0.0007, respectively). Kaplan-Meier survival curves showed statistically significant correlations between 1p36 deletion and decreased overall survival, disease-specific survival, recurrence-free interval, and recurrence-free survival, all of which were maintained in multivariate analysis. We demonstrate that 1p36 deletion can serve as an indicator of unfavorable outcome of patients with salivary gland AdCC.
Keywords: Neoplasm Grading; Young Adult; hybridizace in situ fluorescenční; trans-aktivátory; Prognosis; časové faktory; fúzní onkogenní proteiny; lidské chromozomy, pár 1; mladý dospělý; fúze genů; rizikové faktory; Aged; Chromosome Deletion; Disease-Free Survival; Humans; Kaplan-Meier Estimate; Adolescent; Disease Progression; Neoplasm Recurrence, Local; Oncogene Proteins, Fusion; MYB-NFIB; Adenoid cystic carcinoma; senioři; Male; mladiství; Carcinoma, Adenoid Cystic; Proto-Oncogene Proteins; Treatment Outcome; In Situ Hybridization, Fluorescence; Proportional Hazards Models; lidé středního věku; fenotyp; lidé; chromozomální delece; Adult; výsledek terapie; Risk Factors; adenoidně cystický karcinom; staging nádorů; progrese nemoci; mužské pohlaví; nádorové biomarkery; Immunohistochemistry; Biomarkers, Tumor; Salivary Gland Neoplasms; NFI Transcription Factors; Salivary gland; dospělí; Aged, 80 and over; nádory slinných žláz; Middle Aged; senioři nad 80 let; protoonkogenní proteiny; Kaplanův-Meierův odhad; transkripční faktory NFI; Neoplasm Staging; Trans-Activators; lokální recidiva nádoru; proporcionální rizikové modely; Gene Fusion; stupeň nádoru; Chromosomes, Human, Pair 1; Phenotype; 1p36 locus deletion; Genetic Predisposition to Disease; přežití po terapii bez příznaků nemoci; Time Factors; genetická predispozice k nemoci; imunohistochemie